Electrochemical behavior of bioactive coatings on cp-Ti surface for dental application. (November 2015) - Marques, Isabella da Silva Vieira; Barão, Valentim Adelino Ricardo; Cruz, Nilson Cristino da; Yuan, Judy Chia-Chun; Mesquita, Marcelo Ferraz; Ricomini-Filho, Antonio Pedro; Sukotjo, Cortino; Mathew, Mathew T.
Graphical abstract: Highlights: Bioactive coatings were produced by plasma electrolytic oxidation treatment. Surfaces with higher calcium concentration presented an improved corrosion behavior. Rutile crystalline structure presented better protective barrier properties. PEO treated surfaces allowed optimal spreading and proliferation of hMSCs. Addition of Ag nanoparticles resulted in antibacterial properties. Abstract: The surface characteristics and electrochemical properties of bioactive coatings produced by plasma electrolytic oxidation (PEO) with calcium, phosphorous, silicon and silver on commercially pure titanium were evaluated. PEO treatment produced a porous oxide layer, which improved the surface topography, and enriched the surface chemistry with bioactive elements, responsible for mimicking bone surface. The surfaces with higher calcium concentration presented antibacterial and biocompatibility properties with better responses for corrosion and barrier properties, due to the presence of rutile crystalline structure. PEO may be a promising surface treatment option to improve the electrochemical behavior of dental implants mitigating treatment failures.